Does self-paced learning in mobile flood protection unit construction in virtual reality have advantages over traditional measures? - Querl, Patrick; Chandra, Raymond Leonardo; Berkaoui, Djamel; Castermans, Koen; Nacken, Heribert (Frontiers in Virtual Reality, 2024)
Introduction The study explores the application of virtual reality (VR) in university education, specifically within the context of civil engineering. It aims to investigate the potential of an immersive virtual lab employing self-paced learning for teaching complex tasks. The focus is on the construction of a Mobile Flood Protection Unit (MFPU), traditionally taught through written instructions or video tutorials. Methods An experiment was conducted involving 48 students who were divided into two groups. One group learned to build an MFPU using a VR tutorial, while the other group used a traditional instructional video. The effectiveness of these teaching tools was assessed based on factual and procedural knowledge transfer. Additionally, students' personal perceptions regarding the use of VR software were evaluated. Results The findings indicated a positive effect on factual knowledge transfer when using VR. Moreover, students expressed favorable perceptions towards utilizing VR as a learning tool. Discussion The study suggests that VR can enhance factual knowledge acquisition and is well-received by students in educational settings. However, it also highlights the need for further research to better understand its impact on procedural knowledge gain. Future studies could explore long-term effects and different applications within various fields of education.